Investigating the influence of antenatal education on birth beliefs and delivery methods: a prospective cohort study from Turkey - Sadun Sucu; Serap Topkara Sucu; Çağanay Soysal (BMC Pregnancy and Childbirth)
Abstract Background Women’s prior knowledge about childbirth shapes their ideas about childbirth. The view that childbirth is a physiological process reflects the belief that it is a normal and safe event. Medical process believe that childbirth is dangerous and risky, that it should take place under the careful care of a trained obstetrician because it depends on anatomical conditions. The aim of this study is to identify women’s underlying prenatal and postnatal beliefs about childbirth and to examine the impact of childbirth preparation classes on their beliefs and the impact on the mode of delivery. Materials and methods Demographic and obstetric parameters were compared between August 2023 and August 2024, with the intervention group consisting of 75 patients who attended pregnancy school after the 14th week of pregnancy and the control group, which did not attend pregnancy school, consisting of 150 patients. The pregnant women in the intervention group were surveyed before and after the pregnancy school using the “Birth Belief Scale” questionnaire. It was investigated how the pregnancy school, in which the topics of antenatal care, childbirth, postpartum and newborn care were covered, affected the birth beliefs and what differences there were between the participants and those who did not take part. In this study, which had a twofold aim, firstly, the method of birth and birth characteristics were examined between those who attended pregnancy school and those who did not. Secondly, it investigated the impact of antenatal education on patients’ perceptions of childbirth and their decision as to whether childbirth was a medical process (which should take place under medical supervision) or a natural process. Results A total of 225 patients were included in the study. The primary outcome of the study was that the rate of patients requesting cesarean section during labor because they could not deliver vaginally or could not tolerate the pain during labor was higher in the control group (47.2% versus 73.4%; p = 0.009). There was a statistically significant difference in the indication for cesarean section in both groups and the rate of labor arrest was higher in the control group (8.3% versus 26.6%; p = 0.043). A secondary result of the study was a statistically significant change in the patients’ birth expectations after the training (p < 0.001). Through pregnancy education, the idea that childbirth is a medical intervention was replaced by the idea that it is a natural process. Conclusion This study shows that antenatal education has a positive impact on birth beliefs and birth preferences. It is recommended that educational programs such as childbirth preparation classes be expanded to influence pregnant women’s beliefs about birth and empower them to make informed decisions.